2017
DOI: 10.1002/alr.21968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atopic disease in patients with eosinophilic esophagitis

Abstract: The diagnosis of EoE is associated with the diagnoses of asthma, AR, AD, and food allergies. The high prevalence of these conditions in EoE patients further strengthens the hypothesis of a common pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 47 publications
(56 reference statements)
0
20
0
1
Order By: Relevance
“…[14][15][16] EoE is considered to be a type 2 immune disease that often co-occurs with atopic diseases, including atopic dermatitis (AD), asthma, and food allergies. [17][18][19][20] As such, EoE is characterized by increased levels of the type 2 cytokines, which are critical for promoting cellular responses in patients with EoE. Early mouse studies revealed IL-5 as an important contributing factor for eosinophilic development and tissue infiltration and for remodeling.…”
mentioning
confidence: 99%
“…[14][15][16] EoE is considered to be a type 2 immune disease that often co-occurs with atopic diseases, including atopic dermatitis (AD), asthma, and food allergies. [17][18][19][20] As such, EoE is characterized by increased levels of the type 2 cytokines, which are critical for promoting cellular responses in patients with EoE. Early mouse studies revealed IL-5 as an important contributing factor for eosinophilic development and tissue infiltration and for remodeling.…”
mentioning
confidence: 99%
“…So whether the underlying mechanism of CU and diarrhea involves more than one type of immune response (e.g., IgG mediated) needs further investigation. Besides, AR was usually associated with upper GI diseases, like oral allergy syndrome triggered by pollen, food, or eosinophilic esophagitis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In general, eosinophils have been hypothesized to move to the esophagus in response to various ingested and/or inhaled allergens, thereby associating EoE with allergy-induced diseases. As a result of that, a high prevalence of atopic diseases (e.g., asthma, allergic rhinitis, and atopic dermatitis) and sensitization to food and environment allergens is seen in pediatric and adult EoE populations [9, 64].…”
Section: Etiological Factorsmentioning
confidence: 99%